Portugal's changing defense industry: Is the triple Helix model of knowledge society replacing state leadership model? - Pedro Costa Sim\~oes; António Carrizo Moreira; Carlos Manuel Mendes Dias (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
The defense industry has unique features involving national sovereignty. Despite the characteristics that led to the separation of the military and civil spheres, since the 1990s, the number of dual-use projects has been growing. Taking into account that Portugal is a small European country, this paper analyzes the relationships within the defense industry in order to determine how university-industry-government relationships (the Triple Helix) function in this specific industry. The analysis of 145 projects of the Portuguese Ministry of Defense led to the following conclusions: first, academia was represented in more than 90% of the projects, and 40% of those projects have a dual-use application; second, there is a predominance of knowledge production, dissemination and application, for which the university's institutional sphere is essential and third, the Triple Helix system evolves into a network of relationships that involve projects with both civil and military applications.
Keywords: 650; defense industry; Portugal; triple helix; university-industry-government